2015
DOI: 10.1051/0004-6361/201425519
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived, long-period radial velocity variations in Aldebaran: A planetary companion and stellar activity

Abstract: Aims. We investigate the nature of the long-period radial velocity variations in α Tau first reported over 20 yr ago. Methods. We analyzed precise stellar radial velocity measurements for α Tau spanning over 30 yr. An examination of the Hα and Ca II λ8662 spectral lines, and H photometry was also done to help discern the nature of the long-period radial velocity variations. Results. Our radial velocity data show that the long-period, low amplitude radial velocity variations are long-lived and coherent.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…HD 12648 b becomes the exoplanet detected in the highest declination of 85.7 • so far, and HD 24064 b corresponds to an exoplanet found around one of the largest stars. The planets discovered in five of the six stars larger than HD 24064 were reported in another exoplanet survey program using 1.8 m telescope at BOAO (Lee et al 2013(Lee et al , 2014bHatzes et al 2015).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…HD 12648 b becomes the exoplanet detected in the highest declination of 85.7 • so far, and HD 24064 b corresponds to an exoplanet found around one of the largest stars. The planets discovered in five of the six stars larger than HD 24064 were reported in another exoplanet survey program using 1.8 m telescope at BOAO (Lee et al 2013(Lee et al , 2014bHatzes et al 2015).…”
Section: Discussionmentioning
confidence: 75%
“…The EW variations in the H α line are frequently used as the chromospheric activity indicator, along with Ca II H line (Montes et al 1995;Kürster et al 2003;Lee et al 2012;Hatzes et al 2015). We measured the EW using a band pass of ±1.0 Å centered on the core of the H α line to avoid nearby blending lines (i.e., ATM H 2 O 6561.1, Ti I 6561.3, Na II 6563.9, and ATM H 2 O 6564.2 Å).…”
Section: Chromospheric Activitymentioning
confidence: 99%
“…Aurière et al (2015) also reported a weak magnetic field in Aldebaran (α Tau) but they could not determine the period of its variability. An extense study of RV in this star spanning 20 years by Hatzes et al (2015) reports the presence of a giant planet with a period of ∼ 630 days and modulation of active regions with a period of ∼ 520 days. Finally, a weak magnetic field was also detected in Arcturus (α Boo) by Sennhauser & Berdyugina (2011) with a possible period of 208 days (only 3 measurements were made).…”
Section: Discussionmentioning
confidence: 93%
“…Wilson 1968;Vaughan et al 1978;Baliunas et al 1995;Isaacson & Fischer 2010, and references therein). Some programs using spectrographs lacking blue wavelength coverage and/or targeting cool stars (M dwarfs and giants) have also frequently used the Hα line (Kürster et al 2003;Hatzes et al 2015) and occasionally the Na I D doublet (Gomes da Silva et al 2011;Robertson et al 2015) with success. When possible, it is ideal to measure more than one such tracer, as any star may exhibit multiple activity signals, each of which may (or may not) appear in a given chromospheric line with varying amplitude (e.g.…”
Section: Introductionmentioning
confidence: 99%